Asymmetry of Information, Regulatory Lags and Optimal Incentive Contracts: Theory and Evidence: Discussion - Hall, George R. (Journal of Finance, 1983)
George R. Hall, Asymmetry of Information, Regulatory Lags and Optimal Incentive Contracts: Theory and Evidence: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 431-432